The relationship between personal and organizational problems among prison officers and depression, anxiety and stress - Nurfitri Najwa, Aman Shah (Universiti Malaysia Sarawak, (UNIMAS), 2019)
The purpose of this study is to investigate the relationship between personal and organizational problems among prison officers and depression, anxiety and stress. Historically, this research has been supported in the literature review by prior studies. Furthermore, the method used in this research is the quantitative research design and the data is collected in Jabatan Penjara Betong, Pahang (N= 527). The result showed that there is significant relationship between independent variables and dependent variables. Therefore, all the null hypotheses are rejected. However, only spiritual variable showed weak positive relationship for depression (r=. 460), anxiety (r=. 446) and stress (r=. 492). Meanwhile all the variables showed strong positive relationship. It can be concluded that work and health are the most dominant factors that influence prison officers mental health while the spiritual is the less affective factor.